Uneasy bedfellows? Fusing participatory and psychosocial principles in research with youth workers and young people. (1st October 2019) - Harris, Peter
Abstract : This article charts an attempt to fuse two arguably incompatible formulations of social research; one rooted in a commitment to democratic, participatory practice and the other rooted in a psychosocial epistemological frame. After setting out the broad precepts of the two methodological approaches, the article explores some theoretical and practical tensions that surfaced during a doctoral criminological study examining the desistance-promoting potential of relationships between male youth workers and young men involved in violence. I show how the professional context in which the study was conducted (youth work) afforded the opportunity to work with participants while also retaining a psychosocial epistemological and analytic frame. The article concludes that while the two approaches are likely to remain 'uneasy bedfellows', more researchers in the youth work field might consider adopting a psychosocial standpoint as a means of keeping in sight both the psychic and the social forces imbricated in young people's lives and within their relationships with youth professionals.